Sistem Informasi Pelaporan Rumah Sakit - Prasetya, Handyka; Wibowo, Januar; Sudarmaningtyas, Pantjawati (Jurnal JSIKA, 2012)
Hospital is one of organization which is focus in  health services where is one of the effort is to encourage from the basic level service, like an health center for society. The hospital produces many complicated reports which is needed by the director and health official to keep the process of society service. Beside that, the reports is needed by the director to help analytyc process in order to take a policy. In this moment a hospital has used a system based on computerize to help patient service process. Although the system has not optimalized in utilising because of manual system was still used in hospitas. Because of the problem, hospital needs a new system that is called Reporting Information System, which can produces the reports in table or graphic that can be drilled down.The purpose of this final assignment is making of Reporting Information System that can help the hospital leader in order to analyze the problem dan make a decision. After that system has been created and tested (test case), can be concluded that the system has been appropriated with exptectation.because the initial objective is make a system that can produce the report in table or graphic that can be drilled down . With this system, can help to supervise and analysys data indirectly. Keyword : Reporting Information System, drill down, Test Case